Distribusi Kasus Difteri Berdasarkan Orang, Tempat, Dan Waktu Di Kabupaten Sidoarjo Tahun 2021-2022 - Salsabila, Anmay Shofa Nur; Handayani, Dwi; Qudrotin, Qudrotin (Innovative: Journal Of Social Science Research, 2024)
Diphtheria is an infectious disease caused by Corynebacterium diphtheriae. Causes the formation of thick layer called pseudomembrane which can interfere in breathing. This research was conducted to provide a comprehensive overview of characteristics and distribution patterns of diphtheria cases during 2021-2022. Methods of this research is qualitative research time series design with secondary data. This research describes diphtheria using a descriptive epidemiological case according to person, place and time. The results showed based on age, the highest cases occurred in 1-4 year age (66%). Based on gender, it mostly occurs in men (66%). Based on immunization status, some have complete immunization with an 18 month booster. Based on location, diphtheria incidents often occur in Sukodono District. Based on time, diphtheria cases occurs in March - June and September - December. The discovery of diphtheria cases in Sidoarjo Regency from 2021 tends to fluctuate. In March - June and September - December, diphtheria cases in Sidoarjo Regency experienced a significant increase and decreased at the beginning of the year (January). Most diphtheria sufferers were aged 1-4. Some of them have of complete immunization accompanied by18 month booster. Meanwhile, most cases of diphtheria often occur in men.